Disease-Associated Plasmacytoid Dendritic Cells - Li, Shuang; Wu, Jing; Zhu, Shan; Liu, Yong-Jun; Chen, Jingtao (Frontiers in Immunology, 2017)
Plasmacytoid dendritic cells (pDCs), also called natural interferon producing cells (IPCs) represent a specialized cell type within the innate immune system. pDCs are specialized in sensing viral RNA and DNA by Toll-like receptor-7 and -9 and have the capacity to rapidly produce massive amounts of type 1 IFNs upon viral encounter. After producing type 1 IFNs, pDCs differentiate into professional antigen-presenting cells, which are capable of stimulating T cells of the adaptive immune system. Chronic activation of human pDCs by self-DNA or mitochondrial DNA contributes to the pathogenesis of systemic lupus erythematosis and IFN-related autoimmune diseases. Under steady-state conditions, pDCs play an important role in immune tolerance. In many types of human cancers, recruitment of pDCs to the tumor microenvironment contributes to the induction of immune tolerance. Here, we provide a systemic review of recent progress in studies of the role of pDCs in human diseases, including cancers and autoimmune/inflammatory diseases.